Optimal suturing techniques in patch-bridging reconstruction for massive rotator cuff tears: A finite element analysis - Yuting Zhong; Chengxuan Yu; Sijia Feng; Han Gao; Luyi Sun; Yunxia Li; Shiyi Chen; Jun Chen (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology)
Purpose: To use a finite element method to construct a patch-bridge repair model for massive rotator cuff tears (MRCTs) and investigate the effects of different suture methods and knot numbers on postoperative biomechanics. Methods: A finite element model based on intact glenohumeral joint data was used for a biomechanical study. A full-thickness defect and retraction model of the supraspinatus tendon simulated MRCTs. Patch, suture, and anchor models were constructed, and the Marlow method was used to assign the material properties. Three suturing models were established: 1-knot simple, 1-knot mattress, and 2-knot mattress. The ultimate failure load, failure mode, stress distribution of each structure, and other biomechanical results of the different models were calculated and compared. Results: The ultimate failure load of the 1-knot mattress suture (71.3 N) was 5.6 % greater than that of the 1-knot simple suture (67.5 N), while that (81.5 N) of the 2-knot mattress was 14.3 % greater than that of the 1-knot mattress. The stress distribution on the patch and supraspinatus tendon was concentrated on suture perforation. Failure of the bridging reconstruction mainly occurred at the suture perforation of the patch, and the damage forms included cutting-through and isthmus pull-out. Conclusion: A finite element model for the patch-bridging reconstruction of MRCTs was established, and patch-bridging restored the mechanical integrity of the rotator cuff. The 2-knot mattress suture was optimal for patch-bridging reconstruction of MRCTs.